2022
DOI: 10.1002/eji.202149706
|View full text |Cite
|
Sign up to set email alerts
|

EGFR ligands synergistically increase IL‐17A‐induced expression of psoriasis signature genes in human keratinocytes via IκBζ and Bcl3

Abstract: Various epidermal growth factor receptor (EGFR) ligands are highly expressed in the epidermis of psoriasis lesions, and abnormal EGFR activation appears to be involved in the pathogenesis of psoriasis. However, how EGFR signaling contributes to the development of psoriasis is unclear. Interleukin (IL)‐17A, a critical effector of the IL‐23/IL‐17A pathway, increases the expression of psoriasis signature genes in keratinocytes and plays an essential role in the pathogenesis of psoriasis by inducing IκBζ, a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…HB-EGF rapidly stimulated IL33 mRNA expression commencing 0.5 hours after addition and peaking (>5-fold) at 9 hours ( Figure 3 a) and significantly increased the protein levels of full-length IL-33 time dependently ( Figure 3 b). The IL33 mRNA level decreased sharply from 9 hours to 14 hours after HB-EGF treatment ( Figure 3 a), probably because EGFR signaling returned to the quiescent state after a long duration of stimulation ( Dai et al., 2022a ), and climbed slightly again at 23 hours ( Figure 3 a), which should be attributed to EGFR reactivation after autoinduction and cross-induction by epidermal GF family members ( Shirakata et al, 2010 ). Despite the increased IL-33 expression, HB-EGF stimulation could not exert IL-33 secretion ( Figure 3 c).…”
Section: Resultsmentioning
confidence: 99%
“…HB-EGF rapidly stimulated IL33 mRNA expression commencing 0.5 hours after addition and peaking (>5-fold) at 9 hours ( Figure 3 a) and significantly increased the protein levels of full-length IL-33 time dependently ( Figure 3 b). The IL33 mRNA level decreased sharply from 9 hours to 14 hours after HB-EGF treatment ( Figure 3 a), probably because EGFR signaling returned to the quiescent state after a long duration of stimulation ( Dai et al., 2022a ), and climbed slightly again at 23 hours ( Figure 3 a), which should be attributed to EGFR reactivation after autoinduction and cross-induction by epidermal GF family members ( Shirakata et al, 2010 ). Despite the increased IL-33 expression, HB-EGF stimulation could not exert IL-33 secretion ( Figure 3 c).…”
Section: Resultsmentioning
confidence: 99%
“… 48 Although TGFA did not induce psoriasis-related gene expression, it could significantly enhance the IL-17A-mediated induction of various psoriasis signature genes, including antimicrobial peptides, cytokines, and chemokines. 49 Thus, TGFA production in psoriatic lesions may amplify the inflammation in the lesions. In depression, data regarding role of TGFA is lacking, however, it could be advantageous in supporting the neuroprotective effect in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Il-4, secreted by Th2 cells, is a cytokine closely related to the biological function of AD and continuously activate mast cells to produce more Ig E (44). It has been shown that elevated Th2 cytokines Il-4/Il-13 in AD lesions inhibit keratinocyte differentiation markers (FLG, LOR, keratin 1, and keratin 10) to impair skin barrier function (45). Accordingly, down-regulation of Il-4 expression is an important strategy for the treatment of AD.…”
Section: Discussionmentioning
confidence: 99%